Greater adherence to the Dietary Guidelines for Americans is associated with lower diet-related greenhouse gas emissions but higher costs - Conrad, Zach; Drewnowski, Adam; Love, David C. (Frontiers in Nutrition, 2023)
Few studies have evaluated the sustainability of popular diet patterns in the US, which limits policy action and impedes consumer efficacy to make sustainable dietary changes. This study filled this gap by evaluating the relationship between diet quality, greenhouse gas emissions (GHGE), and diet cost for plant-based, restricted carbohydrate, low grain, low fat, and time restricted diet patterns. Dietary data were retrieved from the National Health and Nutrition Examination Survey (2011-2018, n=8,146) and linked with data on GHGE and food prices from publicly available databases. Diet quality was measured using the Healthy Eating Index-2015. The present study 1) compared the mean diet quality, GHGE, and diet cost between diet patterns, 2) evaluated the association of diet quality to GHGE and diet cost for each diet pattern, and 3) estimated the contribution of food sources to GHGE and diet cost for each diet pattern. Higher diet quality was associated with lower GHGE for the general population and for most diet patterns (P<0.01) except for the plant-based and time restricted diet patterns (P>0.05). Higher diet quality was associated with higher cost for the general population and for all dietary patterns (P<0.01) except the time restricted diet pattern (P>0.05). Protein foods, mostly beef, accounted for the largest share of GHGE (29-40%) and diet cost (28-47%) for all diet patterns except plant-based. Higher diet quality was associated with lower GHGE but was often accompanied by higher diet cost. These sustainability trade-offs can help inform major policy discussions in the US and shed light on further research needs in the area of food systems transformation.